2020
DOI: 10.1007/s00405-020-06401-0
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported factors that influence the vestibular schwannoma treatment decision: a qualitative study

Abstract: Purpose In cases of small- to medium-sized vestibular schwannomas, three management strategies can be opted for: active surveillance, surgery or radiotherapy. In these cases, the patient’s preference is pivotal in decision-making. The aim of this study was to identify factors that influence a patient’s decision for a particular management strategy. Methods A qualitative inductive thematic analysis was performed based on semi-structured interviews. Eighteen patients with small- to medium-sized vestibular schw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Finally, a total of 42 articles were assessed in full text for eligibility, whereof 18 studies were excluded due to not assessing SDM and 2 studies for not being original articles. This resulted in the inclusion of 22 studies: 14 studies identified through literature searches [ 2 , 6 , 16 , 23 , 25 , 28 , 29 , 32 , 35 , 39 , 51 53 , 57 ] and 8 articles through screening of reference lists [ 1 , 5 , 11 , 22 , 34 , 42 , 43 , 54 ] (see Tables 1 and 2 , respectively and see the PRISMA flowchart for more information (Fig. 1 )).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Finally, a total of 42 articles were assessed in full text for eligibility, whereof 18 studies were excluded due to not assessing SDM and 2 studies for not being original articles. This resulted in the inclusion of 22 studies: 14 studies identified through literature searches [ 2 , 6 , 16 , 23 , 25 , 28 , 29 , 32 , 35 , 39 , 51 53 , 57 ] and 8 articles through screening of reference lists [ 1 , 5 , 11 , 22 , 34 , 42 , 43 , 54 ] (see Tables 1 and 2 , respectively and see the PRISMA flowchart for more information (Fig. 1 )).…”
Section: Resultsmentioning
confidence: 99%
“…Of the 22 articles included, 7 focused on SDM in patients with vestibular schwannomas [ 6 , 16 , 28 , 29 , 34 , 35 , 39 ], 6 involved patients undergoing spinal surgery (lumbar herniated disk, lumbar spinal stenosis, spinal stenosis) [ 1 , 2 , 22 , 32 , 42 , 54 ], and 4 included patients with gliomas [ 5 , 11 , 25 , 57 ]. The remaining articles concerned brain metastases, benign brain lesions, Parkinson’s disease, evaluation of neurosurgical care, and one case report on cervical spinal stenosis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This cross-sectional study was part of a more extensive study on long-term VS outcomes in the Netherlands. Participating patients from a questionnaire study in 2014 were reapproached for participation [15]. All patients were diagnosed with unilateral VS between 2003 and 2014.…”
Section: Methodsmentioning
confidence: 99%